13
$\begingroup$

I am trying to calculate the characteristic polynomial of the $n \times n$ matrix $A = \{ a_{ij} = 1 \}$.

  • Case $n=2$: I obtained $p(\lambda)=\lambda^2-2\lambda$ .

  • Case $n=3$: I obtained $p(\lambda)=-\lambda^3+3\lambda^2$.

  • Case $n=4$: I obtained $p(\lambda)=\lambda^4 - 4\lambda^3$.

I guess that for the general case, we have

$$p(\lambda)=(-1)^n\lambda^{n}+(-1)^{n-1}n\lambda^{n-1}$$

I tried to use induction, but it didn't work, unless I've done wrong. Can somebody help me? Or give me a hint?

$\endgroup$
3
  • $\begingroup$ I think it's easier to just compute all of the eigenvalues. The eigenvectors are easy to write down. (Also, you should be using a definition of the characteristic polynomial that makes it monic.) $\endgroup$ Jun 3 '12 at 21:00
  • $\begingroup$ I really dont understand the problem, could any one explain me? $\endgroup$
    – Marso
    Jun 6 '12 at 14:16
  • $\begingroup$ Also see math.stackexchange.com/questions/2853981/… $\endgroup$
    – user538518
    Jul 17 '18 at 0:55
10
$\begingroup$

Note that the matrix $$A = e e^T$$ where $e = \begin{pmatrix}1\\1\\1\\\vdots\\1\\1 \end{pmatrix}_{n \times 1}$.

Hence, $A^2 = \left(ee^T \right) \left(ee^T \right)= e \left(e^T e \right) e^T = n ee^T = nA$.

This clearly indicates that the matrix is a rank one matrix. Hence it must have $n-1$ eigenvalues as $0$. The only non-zero eigen value if $\lambda =n$, since we have $\lambda^2 = n \lambda$ and $\lambda \neq 0$.

$\endgroup$
4
$\begingroup$

The trace is $n$. The eigenvalue $0$ has multiplicity $n-1$. From this we can write down the characteristic polynomial without any computation. Or else we can pick up the eigenvalue of $n$ by noting that the all $1$'s vector times our matrix is the all $n$'s vector.

$\endgroup$
1
  • $\begingroup$ span of 17 seconds, you, Dennis, Marvis. I was going to answer, but. $\endgroup$
    – Will Jagy
    Jun 3 '12 at 21:05
3
$\begingroup$

Using the matrix determinant lemma,

$$\det \left( s \, \mathrm I_n - \mathbb 1_n \mathbb 1_n^\top \right) = s^n \left( 1 - \frac{1}{s} \mathbb 1_n^\top \mathbb 1_n \right) = s^n - n s^{n-1} = s^{n-1} \left( s - n \right)$$


$\endgroup$
0
1
$\begingroup$

Hint: Denote $v=(1,1,...,1)$ and $v_j=(1,0,..,0,-1,0,...,0)$ (all zeroes except for the first, where there is $1$ and the $j$th, where there is $-1$) (all column vectors). What happens when you multiply $A\cdot v$ and $A\cdot v_j$?

$\endgroup$
1
$\begingroup$

We wish to compute the determinant of the $n\times n$ matrix $$ M=\begin{bmatrix} 1-\lambda&1&1&\cdots&1\\ 1&1-\lambda&1&\cdots&1\\ 1&1&1-\lambda&\cdots&1\\ \vdots&\vdots&\vdots&\ddots&\vdots\\ 1&1&1&\cdots&1-\lambda \end{bmatrix}\tag1 $$ Here are two approaches, the second of which uses a generalization of the lemma cited in Rodrigo de Azevedo's answer.


Finding a Similar Matrix

Note that the $n-1$ dimensional subspace orthogonal to $\begin{bmatrix}1&1&1&\cdots&1\end{bmatrix}^\text{T}$ is multiplied by $-\lambda$. (If the subspace is orthogonal to a given vector, we can subtract that vector from each row of the matrix when operating on that subspace.)

$\begin{bmatrix}1&1&1&\cdots&1\end{bmatrix}^\text{T}$ is multiplied by $n-\lambda$. (Just compute it.)

Thus, $M$ is similar to $$ \begin{bmatrix} -\lambda&0&0&\cdots&0\\ 0&-\lambda&0&\cdots&0\\ 0&0&-\lambda&\cdots&0\\ \vdots&\vdots&\vdots&\ddots&\vdots\\ 0&0&0&\cdots&n-\lambda\\ \end{bmatrix}\tag2 $$ Therefore, $$ \det(M)=(-\lambda)^{n-1}(n-\lambda)\tag3 $$


$\boldsymbol{\det(\lambda I_n-AB)=\lambda^{n-m}\det(\lambda I_m-BA)}$

As shown in this answer,

$$ \det(\lambda I_n-AB)=\lambda^{n-m}\det(\lambda I_m-BA)\tag4 $$

Let $A=\begin{bmatrix}1&1&1&\cdots&1\end{bmatrix}^\text{T}$ and $B=A^\text{T}$, then $M=AB-\lambda I_n$.
Furthermore, $m=1$ and $BA=\begin{bmatrix}n\end{bmatrix}$.

$(4)$ then says that $$ \begin{align} \det(-M) &=\det(\lambda I_n-AB)\tag{5a}\\[2pt] &=\lambda^{n-1}\det(\lambda I_1-BA)\tag{5b}\\[2pt] &=\lambda^{n-1}\det(\lambda I_1-\begin{bmatrix}n\end{bmatrix})\tag{5c}\\ &=\lambda^{n-1}(\lambda-n)\tag{5d} \end{align} $$ which, since $\det(-M)=(-1)^n\det(M)$, becomes $$ \det(M)=(-\lambda)^{n-1}(n-\lambda)\tag6 $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.